Tocophobia: overwhelming fear of pregnancy and childbirth - Donel, Jissa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pregnancy and childbirth are a major life process for women. Childbirth is an outstanding life event for every woman. It is considered as normal to experience concern or anxiety to a certain degree, as it can help women to make ready for childbirth. But, if the fear becomes paralyzing and terrifying, it can turn out to be physically and emotionally disabling and give rise to a specific pathology termed as tocophobia. The aim of the present article is to analyze the tocophobic condition and to give a brief overview of the possible approaches currently available to mitigate the tocophobic condition.